Parental hay fever reinforces IgE to pollen as pre‐clinical biomarker of hay fever in childhood. Issue 4 (June 2014) - Hatzler, Laura; Panetta, Valentina; Illi, Sabina; Hofmaier, Stephanie; Rohrbach, Alexander; Hakimeh, Dani; Bauer, Carl P.; Hoffman, Ute; Forster, Johannes; Zepp, Fred; Schuster, Antje; Stock, Philippe; et al.
Abstract Background An early IgE response to grass or birch pollen can anticipate seasonal allergic rhinitis to pollen later in life or remain clinically silent. Objective To identify risk factors early in life that allow discriminating pathogenic from non‐pathogenic IgE responses and contribute to the development of seasonal allergic rhinitis to grass pollen. Methods The German Multicentre Allergy Study examined a birth cohort born in 1990. A questionnaire was yearly administered and blood samples collected at age 1, 2, 3, 5, 6, 7, 10, 13 yr. The definition of the primary outcome grass‐ and birch‐pollen‐related seasonal allergic rhinitis (SARg, SARb) was based on nasal symptoms in June/July and April, respectively. Serum IgE antibodies to Phleum pratense and Betula verrucosae extracts were monitored with immune‐enzymatic singleplex assays. Results Of the 820 examined children, 177 and 148 developed SARg and SARb, respectively. Among healthy children aged 3 or more years, IgE to grass pollen was the strongest risk factor of SARg (OR 10.39, 95%CI 6.1–17.6, p < 0.001), while parental hay fever was the only risk factor in early childhood independently associated with future SARg (1 parent: OR 2.56, 95%CI 1.4–4.5, p < 0.001; 2 parents: OR 4.17, 95%CI 1.7–10.1) and SARb (1 parent OR: 5.21, 95%CI 2.20–12.4, p < 0.001; 2 parents: OR 8.02, 95%CI 2.0–32.9, p < 0.001). Parental hay fever was associated with an increase of the concentration of pollen‐specific IgE in seropositive subjects, after the age of 6 and was also a hallmark of molecularly more complex specific IgE responses to grass or birch pollen at age 6 or older. Conclusions Parental hay fever and specific IgE to grass and/or birch pollen are strong pre‐clinical determinants and potentially good predictors of seasonal allergic rhinitis.